THE EFFECT OF CONSUMER CONFUSION PRONENESS ON WORD OF MOUTH, TRUST, AND CUSTOMER SATISFACTION - Malisa Rosadi; Fandy Tjiptono (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2013)
High-tech products (such as smartphones, notebooks, and tablets) have been characterized as beingincreasingly similar between brands, having too many slightly different choices, and providing complexinformation. In buying these products, many consumers fi nd it diffi cult to differentiate between brands, evaluateover alternatives, and make a good purchase decision. Such situation is known as consumer confusionphenomenon. Previous studies have revealed that consumer confusion is becoming a problem for bothconsumers and marketers. However, the topic still needs further examination, especially in the context of adeveloping country.The present study aims to examine consumers’ general tendency to become confused and its effect onword of mouth, trust and consumer satisfaction. The product context is smartphones, while the sample consistsof 150 university students who had experiences in using or buying smartphones. Nine research hypotheseswere tested using multiple regression analyses. The results indicate that only two of the three consumerconfusion dimensions (i.e. similarity confusion and overload confusion) have signifi cant negative impacts onword of mouth, trust and consumer satisfaction. The other dimension (i.e. ambiguity confusion) was found tohave insignifi cant impacts on the three dependent variables.Keywords: Consumer confusion, word of mouth, trust, consumer satisfaction, smartphone.